Cultivating patriotism: A pioneering note on a Russian dimension of corporate ethics management - Natalia N. Yashalova; Dmitry A. Ruban; Natalia A. Latushko (Administrative Sciences, 2021)
Corporate codes of conduct address various issues, some of which can be country-specific. A tentative analysis of the content of 42 codes of the leading Russian private companies implies that about a quarter of them consider patriotism, which generally matches the significant attention paid to this issue in Russian society. Of 10 companies with the biggest annual revenue, four (40%) consider patriotism in their codes. The main topics are pride in a company's relevance to state development, initiatives, and interests, as well as care for the veterans of the World War II. The present study implies that patriotism can be an important dimension of corporate ethics management in some countries.
Keywords: 350; code of conduct; ethics communication; leading companies; Russia; state focus